Characterization and associated risk factors of Pneumocystis jirovecii pneumonia in patients with AIRD: a retrospective study. (28th December 2021) - Zhao, Zichu; Huang, Yanli; Ming, Bingxia; Zhong, Jixin; Dong, Lingli
Abstract: Objectives: To explore clinical features of autoimmune inflammatory rheumatic disease (AIRD) patients with Pneumocystis jirovecii pneumonia (PJP) and identify potential risk factors and prognostic factors. Methods: AIRD patients who had respiratory symptoms and underwent P. jirovecii detection were identified from the database in our department from November 2018 to October 2020. These patients were categorized into PJP and non-PJP groups according to the diagnostic criteria of PJP. Univariate and multivariate analyses were conducted. Results: A total of 173 patients were enrolled and 46 of them had laboratory-confirmed PJP. Glucocorticoid increased the risk of PJP in a dose-dependent manner. In addition, shorter duration of immunosuppressive therapy (IST), combination therapy with CSA and chronic pulmonary comorbidities were also strongly associated with a higher risk of PJP. Combination of IgM and IgA could well identify AIRD patients with PJP from other AIRD patients with respiratory symptoms, with the optimal cut-off value of −0.96 g/l. Seven of 46 AIRD patients with PJP died (15.2%). A higher level of serum LDH, dyspnoea and ARDS, and the presence of extensive ground glass opacity (GGO) in radiologic examinations were more common in deceased patients. Conclusions: AIRD patients with high-dose glucocorticoid treatment, recent initiation of IST, combination therapy with CSA and history of chronic pulmonary diseases had a greater risk of PJP infection. PJP patients with a higher level of serum LDH, dyspnoea, moderate and severe ARDS, and the presence of extensive GGO in radiologic examinations had poorer prognosis. Trial registration: Chinese Clinical Trial Register; https://www.chictr.org.cn/ ; ChiCTR2100044095.